Acceptability of Cashless Economy after Demonetization in India - Dr. O.P. Pathak; Dr. Bhuwan Gupta (International Journal of Engineering and Management Research, 2019)
Demonetization is the demonstration of stripping a cash unit of its status as legitimate delicate. Demonetisation is fundamental at whatever point there is an adjustment in national money. The old unit of cash must be resigned and supplanted with another money unit. November the eighth, 2016 - the date has become a milestone for the Indian economy. It was a customary day for any Indian, yet then the clock struck 8:15 p.m. also, there was our Prime Minister tending to the compatriots. In a 25-minute long discourse, the Prime Minister had pursued a war against dark cash by pulling back legitimate delicate character of Rupees 500 and Rupees 1000 notes with impact from 12 PM, and giving new Rupees 500 and Rupees 2000 set up. The flooding hazard of phony cash, particularly in high division, can't be focused on enough. This thus, is stored as dark cash and is abused by fear based oppressors for against national and criminal operations. India is as yet known as a money based economy.